“Teaching Mixed Media Techniques in Fine Arts Lessons: Pedagogical and Scientific Approaches” - Qudratova Gulizuhro Otabek qizi, (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines pedagogical and scientific approaches to teaching mixed media techniques in fine arts lessons. Mixed media encourages students to combine various materials, textures, and artistic techniques, fostering creativity, experimentation, and innovative problem-solving. The study explores strategies for integrating traditional and modern media, practical exercises, and interactive pedagogical methods to enhance students’ technical skills, artistic expression, and creative thinking.